Pinkeye in Beef Cattle - Max Irsik (EDIS, 2010)
VM141, a 3-page fact sheet by Max Irsik, describes this common disease of beef cattle that is associated with significant economic losses — causes, transmission, clinical signs, treatment, and prevention. Includes references. Published by the UF College of Veterinary Medicine, July 2009.